Burundi : Second Review Under the Extended Credit Facility-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2013)
The Burundian economy faced several adverse shocks. The government responded by allowing greater exchange rate flexibility and by tightening its monetary policy. The fiscal stance was in line with the program, and program implementation has been broadly satisfactory despite difficult circumstances. Sustaining revenue mobilization remains a top priority. Public financial management needs to be bolstered significantly and the country remains at high risk of debt distress, underscoring the importance of reinforcing debt management. Monetary policy should remain tight until inflation falls.